Trouver sa place dans le secteur académique, un projet de moins en moins attractif pour les doctorants ? - Julien Calmand; Jean-François Giret (Éducation et Socialisation)
In France, a doctorate degree is a necessary condition for accessing permanent positions in higher education and public research. However, it is not a sufficient condition, even if a majority of young Doctorate students wish to stabilize themselves in these jobs. Doctoral training, especially since the creation of doctoral schools, has sought to offer them other professional alternatives. Based on the Cereq surveys on the labour market integration of young doctors, our work highlights a fairly marked drop in the aspirations of young doctors to join the academic sector at the end of their PhD. They also show that the increase in precariousness in this sector seems to affect their career plans by encouraging them to look to other opportunities.